Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1177/1591019916633242
|View full text |Cite
|
Sign up to set email alerts
|

Aortic arch and common carotid artery plaques with soft components pose a substantial risk of cerebral embolization during carotid stenting

Abstract: Objectives A higher rate of embolization is considered a disadvantage of carotid stenting (CAS), when compared with carotid endarterectomy. Plaques in the aortic arch (AA) and the common carotid artery (CCA) may be additional sources of embolization to stented internal carotid plaques during CAS. In this study, we aimed to investigate the relationship between these plaques and intracerebral embolization. Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 32 publications
(67 reference statements)
1
14
0
Order By: Relevance
“…reported that while an EPD may provide partial protection of the ICA to be treated, it does not provide protection against contralateral or posterior fossa embolisation originating from the plaques of the aortic arch. 13 In our cases, postoperative DWI high-intensity lesions in the posterior circulation were identified in the two patients without visible OA–VA anastomosis. Although the postoperative DWI high-intensity lesions might have been caused by embolic agents through the posterior communicating artery, it is also possible that they were caused by plaque fragments from the aortic arch through the VA during catheter manipulation.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…reported that while an EPD may provide partial protection of the ICA to be treated, it does not provide protection against contralateral or posterior fossa embolisation originating from the plaques of the aortic arch. 13 In our cases, postoperative DWI high-intensity lesions in the posterior circulation were identified in the two patients without visible OA–VA anastomosis. Although the postoperative DWI high-intensity lesions might have been caused by embolic agents through the posterior communicating artery, it is also possible that they were caused by plaque fragments from the aortic arch through the VA during catheter manipulation.…”
Section: Discussionsupporting
confidence: 54%
“…Szikra et al reported that soft plaques in the aortic arch and CCA could pose a substantial risk of embolisation during CAS. 13 Kim et al reported that manoeuvres in the aortic arch during CAS play an important role in the occurrence of new ischaemic lesions in the posterior fossa and contralateral ICA territory. 14 These reports may suggest that simpler endoluminal device manipulation in the CCA and aortic arch may be safer regarding the peri-procedural ischaemic stroke risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted a systematic literature review without meta-analysis per Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines [8]. Nineteen studies were identified that discussed perioperative risk in the context of relevant anatomy [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] (Table 1) in addition to fourteen studies [28][29][30][31][32][33][34][35][36][37][38][39][40][41] (Table 2) and fifteen case reports/series [42][43][44][45][46][47][48][49][50][51][52][53][54]…”
Section: Resultsmentioning
confidence: 99%
“…Multivariate analysis was provided in nine series [14,[16][17][18][19][20]22,26,27]. Associated immediate outcomes included the development of post-operative hemodynamic depression (HD), independently predicted by degree of change in pre and post-CAS ICA angulation while plaque morphology and ICA ostium involvement were not significantly associated [26], and the detection of macroscopic intraluminal debris following stent placement, which was predicted by the presence of a heterogeneous echolucent plaque on enhanced carotid ultrasound (CEUS) [27].…”
Section: Studies With Multivariate Analysismentioning
confidence: 99%